PENGARUH NAUNGAN TEHADAP KERAPATAN STOMATA DAN TRIKOMA DAUN SERTA PERTUMBUHAN DAN HASIL DUA VARIETAS TANAMAN KEDELAI (Glycine max (L) Merril) (Effect of Shade on Stomatas and Trichomes Density and Growth of Two Soybean Varieties) - Hutami Indah Pratiwi; Nerty Soverda; . Evita (Bioplantae, 2012)
Development of soybean plants under intercropping standing crops often face many obstacles. Constraints faced by the plants grown in the area under the auspices of the stand, the light intensity is low stress. Stomata and leaf trichomes are character identifier for the adaptation of soybean plants that are in shaded conditions. This study aims to determine the interaction effect of varieties of the shade and density of stomata and leaf trichomes and growth and yield of two varieties of soybean plants. This experiment using split plot design (Split plot) with factorial pattern consisting of 2 factors. The first factor as the main plot (main plot) is a shade (N) which consists of two levels, namely without shade (N0) and 50% shade (N1). Both as a subplot factor (sub plot) is soybean varieties (V) consists of Petek (V1) and Jayawijaya (V2). The data obtained were then processed statistically by analysis of variance, followed by further testing LSD at α = 5% level. Other variables were observed between the density of stomata on the leaf surface, the surface density of trichomes on leaves, total leaf area, number of primary branches, number of pods per plant, number of pods per plant contains, and weight of 100 seeds. The final conclusion is that, 1) decrease low light intensity affect the stomata density and density of leaf trichomes and growth and yield of soybean. Treatment with 50% shade provision increasing the density of trichomes on the surface of soybean leaves but lower total leaf area, number of primary branches, stomatal density on the surface, number of pods per plant, number of pods per plant and weight contains 100 seeds. 2) Provision of shade 50% less likely to cause a low density of stomata and trichome density were higher in tolerant varieties (Petek) compared to susceptible varieties (Jayawijaya). 3) Testing the correlation coefficient between the variable density of stomata and trichomes with variable density growth and yield of soybean showed that the absence of the relationship between the main variables and variable growth or results.Keywords: Soybean, shade, Stomata, trichomes